Christian spirituality : five views of sanctification - Alexander, Donald, 1935-; Ferguson, Sinclair B. (Downers Grove, Ill. : InterVarsity Press, 1988)
The nature of Christian spirituality has been widely debated throughout the history of the church. The doctrine of sanctification was one of the main fissures separating Luther from the Catholic Church. Even today different groups of Protestants disagree on how we draw closer to God. What distinguishes the different poisitions and what exactly is at stake in these recurring debates?
To answer these questions Donald L. Alexander, professor of biblical theology at Bethel College, has brought together five scholars that represent each of the main historical Protestant traditions: * Gerhard O. Forde on the Lutheran vew * Sinclair B. Ferguson on the Reformed view * Laurence W. Wood on the Wesleyan view * Russell P. Spittler on the Pentecostal view * E. Glenn Hinson on the Contemplative view.
With an introduction by Alexander and responses to each of the main essays by the other contributors, this book provides a helpful and stimulating introduction to an important doctrine of the church.
The Lutheran view / by Gerhard O. Forde -- Responses / by Sinclair B. Ferguson, Laurence W. Wood, Russell P. Spittler, E. Glenn Hinson -- The Reformed view / by Sinclair B. Ferguson -- Responses / by Gerhard O. Forde, Laurence W. Wood, Russell P. Spittler, E. Glenn Hinson -- The Wesleyan view / by Laurence W. Wood -- Responses / by Gerhard O. Forde, Sinclair B. Ferguson, Russell P. Spittler, E. Glenn Hinson -- The Pentecostal view / by Russell P. Spittler -- Responses / Gerhard O. Forde, Sinclair B. Ferguson, Laurence W. Wood, E. Glenn Hinson -- The contemplative view / by E. Glenn Hinson -- Responses / by Gerhard O. Forde, Sinclair B. Ferguson, Laurence W. Wood, Russell P. Spittler.
Includes bibliographical references.
Keywords: Sanctification -- Christianity -- Comparative studies; Holiness -- Christianity -- Comparative studies; Spirituality -- Comparative studies